Approximation of Differentiable Periodic Functions by Their Biharmonic Poisson Integrals - Zhyhallo, K. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We determine the exact values and asymptotic decompositions of upper bounds of approximations by biharmonic Poisson integrals on classes of periodic differentiable functions.